Taming the flames: the role of emotional intelligence in controlling moral outrage among medical students - El Tarhouny, Shereen; Saif, Hossam Abou; El Sawaf, Zeinab; Mansour, Tayseer (Frontiers in Medicine, 2026)
BackgroundEmotional intelligence (EI) is increasingly recognized as a critical competency for medical students, enabling them to effectively regulate emotions, navigate complex ethical dilemmas, and maintain professional integrity. However, the specific role of EI in moderating moral outrage, a strong emotional response to perceived ethical violations, remains underexplored. Given the potential for unchecked moral outrage to destabilize professional conduct and compromise patient care, understanding how EI influences, particularly among medical students in Egypt.MethodsA cross-sectional study assessed Emotional intelligence and moral outrage control among 478 medical students in Egypt, using validated, adapted instruments: a 15-item short form of the Schutte Self-Report Emotional Intelligence Test (SSEIT) and a newly developed 10-item Moral Outrage Scale (MOS) based on situational vignettes relevant to medical training. EI scores were categorized as low (15–29) or high (30–45), while moral outrage control was grouped as low (≤18) or high (19–30). Statistical analyses included frequencies, percentages, and chi-square tests to examine associations between EI and moral outrage regulation.ResultsThe majority of participants (79.92%) exhibited high emotional intelligence. A statistically significant positive correlation was found between emotional intelligence and moral outrage control (r = 0.62, p < 0.001). Regression analysis shows EI predicted 39% of the variance in moral outrage control (R2 = 0.33, p < 0.001). Students with high EI demonstrated significantly better capacity to regulate responses to ethically challenging situations.ConclusionThis study found that Emotional intelligence plays a significant role in shaping how medical students manage moral outrage. Medical students with higher emotional intelligence (EI) exhibited a significantly greater ability to regulate moral outrage, demonstrated by more controlled and constructive responses to ethical challenges. Integrating EI training into medical curricula could enhance ethical sensitivity and reduce the risk of maladaptive emotional responses in clinical practice. This study utilized self-reported measures, employed a cross-sectional design that restricts the ability to draw causal conclusions, and involved participants from a limited number of institutions, which may impact the generalizability of the findings.